PENGARUH WORD OF MOUTH (WOM) DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS AS PHONECELL SUKARAME - Fattah F, A’lan; Mirandha, Yovie; Fadil, Ahmad; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2022)
Word of Mouth is also known as "mouth-to-mouth marketing" or word-of-mouth communication is a verbalcommunication between one person and another that can be done face-to-face or through electronic media. Productcompleteness is an important concept in supply chain management and marketing. Product completeness refers toall elements or features included in a product or service to meet customer needs, expectations, and satisfaction. Andconsumer purchasing decisions are influenced by various factors, including personal, economic, functional,cultural, and psychological factors. These factors can affect the consumer decision-making process, which includesrecognizing a need, finding information, evaluating alternatives, making purchasing decisions, and evaluating thepost-purchase experience